2022
DOI: 10.3390/antibiotics11060822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoroquinolone Use in Primary Care on the Development and Gradual Decay of Escherichia coli Resistance to Fluoroquinolones: A Matched Case-Control Study

Abstract: The reversibility of bacterial resistance to antibiotics is poorly understood. Therefore, the aim of this study was to determine, over a period of five years, the effect of fluoroquinolone (FQ) use in primary care on the development and gradual decay of Escherichia coli resistance to FQ. In this matched case–control study, we linked three sources of secondary data of the Health Service of the Autonomous Province of Bolzano, Italy. Cases were all those with an FQ-resistant E. coli (QREC)-positive culture from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Kurotschka and colleagues showed that resistance of Escherichia coli gradually decreased over time after fluoroquinolone use declined. 33 Similar results were shown in previous studies. 34 35 Thus, a positive effect on resistance rates of E coli can be expected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Kurotschka and colleagues showed that resistance of Escherichia coli gradually decreased over time after fluoroquinolone use declined. 33 Similar results were shown in previous studies. 34 35 Thus, a positive effect on resistance rates of E coli can be expected.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, data inform guidelines for treatment recommendations. Kurotschka and colleagues showed that resistance of Escherichia coli gradually decreased over time after fluoroquinolone use declined 33. Similar results were shown in previous studies 3435.…”
Section: Discussionsupporting
confidence: 75%
“…While multiple drugs may all adequately treat an indication, stewardship efforts to optimize medication selection based on evidence-directed practice may improve overall appropriate antibiotic use and minimize collateral consequences such as the development of resistance, the risk of which may persist beyond the immediate antibiotic course. One recent case–control study evaluating fluoroquinolone resistance in Escherichia coli found that receiving at least one fluroquinolone prescription preceding the diagnosis of resistance was associated with a higher risk of fluoroquinolone-resistant E. coli colonization or infection, with the risk of resistance highest in the first year after the antibiotic is taken (OR 2.67) and progressively decreasing to undetectable after two years (OR 1.09) [ 39 ]. Thus, judicious drug selection to spare unnecessary or overly broad antibiotic use serves as an important opportunity to potentially curtail some of these repercussions.…”
Section: Interventional Approach To Stewardshipmentioning
confidence: 99%
“…Several meta-analyses have demonstrated a direct relationship between exposure to certain antimicrobial classes and microbiological resistance [12]. Cephalosporins and betalactams combined with beta-lactamase inhibitors are potential selectors of resistant strains, 3 of 17 but fluoroquinolones (FQ) are the most concerning and dangerous antibiotics [13,14]. Recent guidelines from the Infectious Diseases Society of America (IDSA) recommend reserving their use to protect the ecosystem from MDR and harm [15].…”
Section: Introductionmentioning
confidence: 99%